A case study of parental involvement in orientation and mobility of visually impaired children in Pakistan - Abdul Manaf, Umi Kalthom; Malik, Shazia (Department of Secondary Education, 2019)
This paper examined on the role of parental involvement in orientation and mobility of visually impaired children (VIC) in Pakistan. It deals with how parents are involved in Orientation and Mobility (O&M) and how they justify their involvement in O&M for their VIC. Literature has seen that Pakistani VIC are lacking parental involvement in their O&M. Such practices of O&M are deemed essential for their independence. Moreover, their O&M practices require proper training. The lack of research on the part of parental involvement in the training of visually impaired population, needs for more consideration in this area, especially in Pakistan (Aziz, 2007). Data was collected through interviews of five parents of visually impaired children. After completing the data collection process, interviews were transcribed verbatim and codes and categories were developed to get emerging themes from data manually using a cross case analysis. The findings of this research would be beneficial for both parents and their visually impaired children in understanding the independence needs of such children. It is hoped that the findings of the study also will help the management of special education to plan and guide their programs to empower the parents and provide them with the significance of their involvement in the practices of O&M for their children. As for the visually impaired children, it is hoped that their independence in the environment would be enhanced with the help of their parental involvement in O&M as O&M is the compulsory subject of the Expanded Core Curriculum (ECC). ECC is accepted as the curriculum for VIC internationally, but in Pakistan there is not much focus on ECC rather sighted child's curriculum is adopted for VIC. This research proposes a study to focus ECC application in Pakistan for VIC.